A Design And Analysis Of Crown Slot Patch Antennas For 5g Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, A highly compact (volume of only 7 x 7x1.6mm3) crown slot patch antenna, operating at 28GHz (5G mobile applications) and 34GHz (higher satellite band application ) is presented. A structure of antenna is integrated with heptagon radiator and crown shaped slot on the radiating element. The proposed configuration has The antenna has S11